Uncertainty Reduction Theory in Building Early Marriage Intimacy in Argasunya Village, Harjamukti District, Cirebon City - Inayah, Dewi; Sulaiman, Anton; Shittu, Abdullateef (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
Interpersonal communication is important in life, including in marriage. Early marriage remains an issue in Indonesia, with various contributing factors. Islam views marriage as a positive thing to build a harmonious family. Effective communication plays an important role in building intimacy in early marriage couples. Uncertainty Reduction Theory is relevant to understanding how communication can reduce uncertainty and increase intimacy. This study aims to understand the process of Uncertainty Reduction Theory in Building Intimacy in Early Marriage in Argasunya Village, Harjamukti District, Cirebon City and to identify the strategies of Uncertainty Reduction Theory in Building Intimacy in Early Marriage in Argasunya Village, Harjamukti District, Cirebon City. This research uses a descriptive qualitative approach. This approach aims to explore and capture the social situation comprehensively, broadly, and deeply. Qualitative research produces descriptive data in the form of written or spoken words from people and observed behaviors. It focuses on social phenomena, feelings, and perceptions of participants. This approach was chosen to obtain complete information about building intimacy in early marriages in Argasunya Village. The data collection technique was carried out by three main methods, namely observation, interview, and documentation. The data analysis in this study uses a descriptive analytical method consisting of three main stages, namely data reduction, data presentation, and conclusion drawn. The findings of this study are that in Argasunya Village, Cirebon, early marriage is common. Couples use passive, active, and interactive communication strategies based on Uncertainty Reduction Theory to build intimacy. They adjust their strategies according to the stages of marriage, overcoming obstacles such as differences in background and uncertainty. It is hoped that these findings can add to the literature of the Islamic Communication and Broadcasting Study Program, Faculty of Da'wah and Communication, Bunga Bangsa Islamic University of Cirebon in particular. The implications of the results of this study show how early marriage couples in Argasunya Village build intimacy through tailored communication strategies based on Uncertainty Reduction Theory, providing valuable insights for the development of interventions that can improve young couples' relationships in specific religious and socioeconomic contexts. The recommendation is that the local government of Cirebon City, especially in Argasu Village, develop a mentoring program for early marriage couples that focuses on improving interpersonal communication skills with the Uncertainty Reduction Theory approach